2014
DOI: 10.1093/nar/gku263
|View full text |Cite
|
Sign up to set email alerts
|

CDK2-dependent phosphorylation of Suv39H1 is involved in control of heterochromatin replication during cell cycle progression

Abstract: Although several studies have suggested that the functions of heterochromatin regulators may be regulated by post-translational modifications during cell cycle progression, regulation of the histone methyltransferase Suv39H1 is not fully understood. Here, we demonstrate a direct link between Suv39H1 phosphorylation and cell cycle progression. We show that CDK2 phosphorylates Suv39H1 at Ser391 and these phosphorylation levels oscillate during the cell cycle, peaking at S phase and maintained during S-G2-M phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…KMT1A is a phosphoprotein and that phosphorylation modulates its function [55–57]. We found that KMT1A phosphorylation increases in myoblasts on induction of differentiation, a finding consistent to our previous study [26].…”
Section: Discussionsupporting
confidence: 91%
“…KMT1A is a phosphoprotein and that phosphorylation modulates its function [55–57]. We found that KMT1A phosphorylation increases in myoblasts on induction of differentiation, a finding consistent to our previous study [26].…”
Section: Discussionsupporting
confidence: 91%
“…24 Cdk2-mediated phosphorylation of SUV39H1 at S391 during S phase leads to its dissociation from chromatin and causes heterochromatin replication. 25 The dynamic distribution during mitosis implies that SUV39H1 may play a role during cell division that has indeed been confirmed by gene disruption studies in mice.…”
Section: Biochemical Propertiesmentioning
confidence: 77%
“…The PCR product was then inserted into pCMV-3Tag-6 Flag epitope-tagging mammalian expression vectors (Stratagene, La Jolla, CA). The lysine (K) to arginine (R) mutants KDM4A K463R, KDM4A K471R, KDM4A K549R, KDM4A K999R, KDM4A K1036R, and KDM4A K3R (combination of K463R/ K471R/K549R) plasmids were generated by PCR-based mutagenesis as previously described (Park et al 2014). Human SUMO1 and SUMO1 lacking a C-terminal GlyGly (SUMO1-ΔGG) were amplified by PCR and subcloned into pCMV-3Tag-2A myc-tagging mammalian expression vectors (Stratagene).…”
Section: Plasmids and Antibodiesmentioning
confidence: 99%
“…Cell lysate protein (500 µg) was incubated with FLAG M2 agarose (Sigma) overnight at 4°C as previously described (Park et al 2014), the beads were then washed five times with lysis buffer, and the immunoprecipitates were eluted by boiling the beads in 2× SDS sample buffer for 10 min. The immunoprecipitates were resolved by SDS-PAGE and transferred onto PVDF membrane for immunoblotting.…”
Section: Immunoprecipitation and In Vivo Sumoylation Assaymentioning
confidence: 99%
See 1 more Smart Citation